Assessment the Groundwater on A Basis of Analysis of Correlation Matrices - Rajabova Nilufar Davlatboy kizi; Sherimbetov Vafabay Khalilullaevich (Periodica Journal, 2023)
Groundwater which is distributed at a depth of 13-17 meters in Amudaryo district, was done evaluated on a basis of changeful parameters. The object was analyzed on account of Pearson correlation matrix and its monitoring was carried out by virtue of statistical analysis of several parameters (hydrogen indicators, pH, Cu, Cl- , NO3 2 , SO4 2- , total solids).
Keywords: “groundwater”; “tap water”; total solids